Salinization, gypsum content and pollution of soils in the Zhezkazgan Botanical Garden 80 years since its organization and start of irrigation - Golovanov, D.L.; Kravchenko, E.I.; Kusherbayev, S.; Amanzholov, A.; Myrzabayev, A.B.; Ishmuratova, M.Yu.; Matveev, A.N.; Mushnikova, N.A.; Dobrydneva, L.V. (Fundamental and Experimental Biology, 2022)
This study aims to identify changes in the properties of brown arid soils under irrigation conditions and the effects of emissions from enrichment and copper smelting plants. The article analyzes the current state of salinization, humus content, heavy metals in the soils of the Zhezkazgan Botanical Garden, located in the zone of intensive anthropogenic emissions. The change in soil properties determines the resistance of cultivated plants to natural and anthropogenic stresses, as well as the quality of grown products. The botanical garden has selected plants that can actively grow under irrigation in sharply continental conditions. For 80 years of operation, partial dissolution of gypsum, redistribution of salts, and an increase in humus content have been noted. The use of polluted waters of the Kengir River as an irrigation source has led to an increase in the content of gross and mobile forms of Cu and Pb in the surface horizons. The results obtained allow us to assess the speed and direction of gypsum redistribution, recommend the transition to water -saving drip irrigation technologies with simultaneous sedimentation and removal of suspended matter from irrigation water.